The Role of Modern Advertisements in Reducing the Spread of Drugs Among Youth (Journal of the College of Basic Education, 2026)
The issue of drugs is considered one of the most dangerous challenges facing society. The increasing number of awareness advertisements has become one of the methods used to reduce its spread. Internet advertisements have been widely used to publish these awareness campaigns. Therefore, the researcher conducted the study entitled (The Role of Modern Advertisements in Reducing the Spread of Drugs Among Youth), which consisted of four chapters. The first chapter included the research problem, represented by the following question: (What is the role of modern advertisements in reducing the spread of drugs among youth?). The aim of the research was defined as: (to identify the role of modern advertisements in increasing awareness about the dangers of drugs among youth). To achieve this goal, the first chapter (theoretical framework) included two sections. In the third chapter, concerning research procedures, the researcher followed the descriptive-analytical method. The research community included advertisements published on the Internet during the period (1/1/2025 – 1/5/2025), with a total of (20) drug-related advertisements selected for their variety of ideas to suit the research purposes. The study population of respondents was taken from students of Dar Al-Hikma Secondary School for Boys, sixth grade, totaling 200 students. A systematic random sample of (25%) was selected, resulting in a sample of (50) students. This stage was chosen because it is suitable for the age group targeted by the research material. As for research tools, the researcher used a questionnaire form. The fourth chapter included a set of results, conclusions, recommendations, and suggestions.Main Results:1 – The majority of respondents found Internet advertisements to be the most effective type in raising awareness about drugs, with 78% of the total sample. 2 – Most respondents believed that the Internet surpassed other media as an effective means of reaching the target audience, with 90% of the total sample. Main Recommendations:1 – Intensify the dissemination of awareness advertisements against drugs to reduce their wide spread among youth. 2 – Publish awareness advertisements against drugs via the Internet to reach the target audience at a high rate, due to the widespread use of the Internet by society.